In Vivo and in Vitro Selection of Mitogen Responsive Lymphocytes in Patients with Chronic Lymphocytic Leukemia - Blomgren, H.; Jondal, M.; Johansson, B. (Acta radiologica. Therapy physics biology, 1976)
The in vitro mitogen response of blood lymphoid cells from patients with chronic lymphocytic leukemia was observed to be low compared to lymphocytes from healthy subjects. However, highly responsive cells could be separated from the blood of such patients by a buoyant density centrifugation technique and such reactive cells were found to be enriched by treating the patients with chemotherapy or splenic irradiation.